Kultura druženja chat room generacije - Oblak, Tanja (Javnost (Ljubljana), 2004)
The article explores the meaning of specific, emerging sites for communication in the context of everyday life among the young generation. Within the so-called chat-rooms, a dynamic, talkative culture is being developed, and a new context for interpersonal relations is being built. Through analyses of several debates and concrete empirical studies, the author illustrates the potentials and possible implications of these communication sites. At least three types of interpersonal culture are significant for the new "chat-room" generation: they offer a refuge in a fantasy world, a search for therapeutic ties and friendship, and experimentation with intimate relationships. A common characteristic of these forms of social relationships is their false image of power offered to participants.
Keywords: mladina; družabno življenje; communication; komuniciranje; elektronski mediji; komunikacijska tehnologija; računalniška omrežja; množične komunikacije; družbeno vedenje